ETHNOPHARMACOLOGICAL AND PRECLINICAL STUDY OF DIURETIC ACTIVITY INMEDICINAL AND FOOD PLANTS USED BY CUBAN POPULATION - Pérez, Maykel; Boffill, Maria A.; Morón, Francisco J.; Sueiro, Mario L.; Marrero, Evangelina; Betancourt, Emoe (Emirates Journal of Food and Agriculture, 2011)
In Cuba, there exists about 179 medicinal plants which are known because of their diuretic properties. To evaluate the diuretic activity attributed to six medicinal plants used by the Cuban population: Ocimum basilicum L., Parthenium hysterophorus L. (medicinal plants), Justicia pectoralis Jacq., Plectranthus amboinicus (Lour.) Spreng, Allium cepa L. and Citrus aurantium L. (medicinal and food plants). Aqueous extracts were prepared from the dry drug of the first four plants mentioned above, and in the case of A. cepa and C. aurantium natural juice were taken for the study. Eight Sprague-Dawley male rats were taken randomnly and eight homogeneous groups were formed: group 1, received 20 mg/kg of furosemide (reference drug); group 2, received NaCl (0.9%), and groups from 3 to 8 received doses of 400 mg/kg BW, based on extracts determination of total solids, this dose volume was completed with physiological saline solution to achieve an hydrosaline overcharge in a constant total administration volume of 40 ml/kg PV, in all experimental groups as described in literature, using in all of the cases an 16 G intragastric cannula. Rats were placed in metabolic cages, where urinary excretion during the ½, 1, 2, 3, 4, 6 and 24 hours was measured and diuretic activity and action were later mathematically calculated. There was observed an increase of the urine volume in treated groups in relation with the negative control group. Urinary excretion, action and diuretic activity were superior in the experimental groups corresponding to O. basilicum L. and A. cepa and similar to reference diuretic drug. This research allowed us to conclude preliminarily that from the six studied plants, O. basilicum and A. cepa exerts best diuretic activity (moderated).